Host genetic variants and gene expression patterns associated with Epstein-Barr virus copy number in lymphoblastoid cell lines. - Charlotte J Houldcroft; Velislava Petrova; Jimmy Z Liu; Dan Frampton; Carl A Anderson; Astrid Gall; Paul Kellam (PLoS ONE, 2014)
Lymphoblastoid cell lines (LCLs) are commonly used in molecular genetics, supplying DNA for the HapMap and 1000 Genomes Projects, used to test chemotherapeutic agents, and informing the basis of a number of population genetics studies of gene expression. The process of transforming human B cells into LCLs requires the presence of Epstein-Barr virus (EBV), a double-stranded DNA virus which through B-cell immortalisation maintains an episomal virus genome in every cell of an LCL at variable copy numbers. Previous studies have reported that EBV alters host-gene expression and EBV copy number may be under host genetic control. We performed a genome-wide association study of EBV genome copy number in LCLs and found the phenotype to be highly heritable, although no individual SNPs achieved a significant association with EBV copy number. The expression of two host genes (CXCL16 and AGL) was positively correlated and expression of ADARB2 was negatively correlated with EBV copy number in a genotype-independent manner. This study shows an association between EBV copy number and the gene expression profile of LCLs, and suggests that EBV copy number should be considered as a covariate in future studies of host gene expression in LCLs.